Hegel as pyrrhonist or the dawn of philosophical science - Vieweg, Klaus (Estudios de Filosofía, 2002)
Hegel maintains that Philosophy needs to become invulnerable to the Skeptic objections from isosthenia. This is achievable only by comprehending the authentic Skeptícism. Two steps render the first Pyrrhonism radical and universal -Freedom of the Character and Freedom of the Thought. Hegel's strategy consists in including or overcoming the Skepticism into a way of life and thought. Therefore, a Skeptic negativity must also be assumed. An incorporatíon of such negative Skepticism is to be done both in the epistemic and the practical-ethical level. As a result, the weaknesses of Pyrrhonism are overcome. The Pyrrlzonic legacy in Hegel's ideas is evident especially in the way he sees the beginning of philosophy, i. e., the decision to "think with all wholesomeness ".